Frontotemporal dementia in a Brazilian Caucasian kindred with the C9orf72 mutation - Takada, Leonel T. (2012)
OBJECTIVE: Describe the clinical features of a Brazilian C9orf72 frontotemporal dementia – amyotrophic lateral sclerosis (FTD-ALS) kindred, and compare them to other reported C9orf72 families and FTD-ALS causing mutations. DESIGN: Report of a kindred. SETTING: Dementia center at an University hospital. PATIENTS: One kindred encompassing 3 generations. RESULTS: The presence of a hexanucleotide (GGGGCC) expansion in C9orf72 was confirmed by repeat-primed PCR and Southern blot. The observed phenotypes were behavioral variant FTD and ALS with dementia, with significant variability in age of onset and duration of disease. Parkinsonian features with focal dystonia, visual hallucinations and more posterior atrophy on neuroimaging than is typical for FTD were seen. CONCLUSIONS: bvFTD due to C9orf72 expansions displays some phenotypic heterogeneity, and may be associated with hallucinations, parkinsonism, focal dystonia, and posterior brain atrophy. Personality changes may precede by many years the diagnosis of dementia and may be a distinguishing feature of this mutation.